2020
DOI: 10.1073/pnas.1922840117
|View full text |Cite
|
Sign up to set email alerts
|

Vapor isotopic evidence for the worsening of winter air quality by anthropogenic combustion-derived water

Abstract: Anthropogenic combustion-derived water (CDW) may accumulate in an airshed due to stagnant air, which may further enhance the formation of secondary aerosols and worsen air quality. Here we collected three-winter-season, hourly resolution, water-vapor stable H and O isotope compositions together with atmospheric physical and chemical data from the city of Xi’an, located in the Guanzhong Basin (GZB) in northwestern China, to elucidate the role of CDW in particulate pollution. Based on our experimentally determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Researchers and practitioners are gradually gaining new knowledge about contributors to PM 2.5 . For instance, a recent study finds that water vapor from combustion can enhance the formation of secondary aerosols (Xing et al 2020). At a State Council meeting led by Premier Li Keqiang in September 2020, experts also identified the overuse of ammonia in treating NO x emissions as a cause for haze.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and practitioners are gradually gaining new knowledge about contributors to PM 2.5 . For instance, a recent study finds that water vapor from combustion can enhance the formation of secondary aerosols (Xing et al 2020). At a State Council meeting led by Premier Li Keqiang in September 2020, experts also identified the overuse of ammonia in treating NO x emissions as a cause for haze.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up our simulation result of the heavy haze episode, we found that the primary and secondary sulfate contributed 3.1% and 9.4%, respectively, to the total PM 2.5 in Xi'an (2). There is an additional 42.0% of the PM 2.5 coming from nitrate, ammonium, and SOA (2). Many of the secondary PM 2.5 formations are known to be sensitive to relative humidity (9).…”
mentioning
confidence: 85%
“…When measuring atmospheric water vapor isotope composition in our field campaign both industrial and residential contributions of CDW were included. It should be mentioned that Xing et al (2) do not attribute the cause of the observed correlation to the CDW fraction or any individual factors. In fact, we highlight the potential positive feedback between haze events and the increase of CDW fraction in air moisture.…”
mentioning
confidence: 91%
See 2 more Smart Citations